Coupled hydro-aero-turbo dynamics of liquid-tank system for wave energy harvesting: numerical modellings and scaled prototype tests - Zhang, Chongwei; Zhu, Xunhao; Zhang, Cheng; Huang, Luofeng; Ning, Dezhi (Elsevier, 2025)
The wave-energy-harvesting (WEH) liquid tank with an air-turbine system has distinct advantages in survivability and durability. Its air-turbine effects have long been simplified using orifices, perforated plates, or empirical formulae. This study proposes an integrated numerical model to couple with actual turbine motions. A series of experiments are conducted on a scaled prototype of the WEH liquid tank with an impulse air turbine system. Benchmark experimental data are obtained for validation of the numerical model. The proposed integrated numerical model accurately reproduces the experimental observations. The effects of turbine parameters on the coupled hydro-aero-turbo behavior are systematically investigated. The optimal power take-off damping for the WEH liquid tank is identified. A multi-layered impulse air turbine system (MLATS) is creatively introduced into the liquid-tank system to explore its capability in improving efficiency and reliability. Compared to the single-rotor case, the MLATS with three rotors can increase the averaged power output of the WEH liquid tank by up to 40%. Through a series of failure tests, a three-rotor turbine shows greater reliability than a conventional single-rotor turbine.
Keywords: Energy; 4008 Electrical engineering; 4012 Fluid mechanics and thermal engineering; 4017 Mechanical engineering; Wave energy; Liquid sloshing; Wave energy converter; Power take-off; ocean energy